Diagnosis and therapy of neuroendocrine neoplasms of the gastrointestinal tract - Deptała, Andrzej; Czerw, Aleksandra Izabela (Family Medicine & Primary Care Review, 2016)
A neuroendocrine neoplasm (NEN) is a tumor that originates in neuroendocrine cells capable of producing peptides or amines. Neuroendocrine neoplasms of the digestive system are also referred to as gastroenteropancreatic neuroendocrine neoplasms (GEP NEN) and constitute a heterogeneous group of growths originating from at least 15 types of specialized cells spread throughout the stomach, small intestine, large intestine, and pancreas. Some GEP NENs have a secretory capacity and are referred to as hormonally active NENs. However, the majority of GEP NENs are hormonally inactive. GEP NENs are relatively rare neoplasms (around 2% of the overall number of neoplasms of the digestive system) with an incidence of around 6 cases per 100,000 per year. In the diagnosing NENs, imaging methods based on morphology (such as USG, EUS, CT, MRI, and endoscopy) and functional techniques (like somatostatin receptor scintigraphy and gallium isotope PET-CT) are applied. The type of treatment for NEN is determined by the degree of malignancy, stage, omatostatin receptor expression, symptoms of hypersecretion syndrome, general health of patient, and presence of concomitant diseases. Therapeutic approaches to GEP-NEN include combinations of the following methods: surgery, ablation techniques, somatostatin eceptor-based therapy (nonconjugated analogues of somatostatin – “cold” SSTA; and analogues conjugated with a radioactive isotope of yttrium (90Y) or lutetium (177Lu) – “hot” SSTA), chemotherapy, and molecular targeted therapy (everolimus, sunitinib).